Growth and Yield of Shallots at various Plant Spacing in Ultisol Dry Land - Budiyati Ichwan; Eliyanti Eliyanti; Zulkarnain Zulkarnain; Susilawati Susilawati; Indra Permana (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2023)
Plant spacing was one method that could be used to boost plant populations. In order to increase shallot (Allium ascalonicum L.) production and productivity on less-than-ideal ground, such as dry land in Jambi. This study aimed to examine the effects of various plant spacing on the growth and yield of shallots and to obtain plant spacing that provides the best shallot growth and yield. This research was conducted at the Teaching and Research Farm, Faculty of Agriculture, University of Jambi. The design used a   Randomized   Block   Design (RBD) consisting of four treatments with six replications. The treated plant spacing was:10 cm x 10 cm; 15 cm x 15 cm; 15 cm x 20 cm; and 20 cm x 20 cm. Various plant spacing affected the shallot growth and yield, and a plant spacing of 15 cm x 15 cm provided better growth and yield compared to any other plant spacing, with the number of leaves per plant, the weight of bulbs per clump, and the weight per bulb of 22, 49, 49.84, and 13.94 g   successively.